Enhanced Rice Yield Prediction in Indonesia with Integrated Climate and Agricultural Data Using Decision Tree Regression - Tegar Arifin Prasetyo; Samuel Jefri Siahaan; Usman Efendi; Mesya Angeliqa Hutagalung; Amalia Nur Alifah (Register: Jurnal Ilmiah Teknologi Sistem Informasi, 2026)
Rice is central to Indonesia’s food security, yet provincial yields are highly sensitive to climatic variability, making reliable forecasting essential for national planning and improving farmer welfare. Most prior Indonesian yield models rely on rainfall and temperature data and omit sunlight exposure duration, which is a limiting factor for photosynthesis in the humid tropics where solar radiation, not temperature, often constrains productivity. This study develops a province-level rice yeild prediction model based on Decision Tree Regression (DTR) that integrates climate data from the Meteorology, Climatology, and Geophysics Agency (BMKG) with agricultural statistics from the Central Statistics Agency (BPS). The dataset comprises data from 34 provinces covering the period from 2018 to 2023 (204 province-year observations), with year, harvested land area, rainfall, and sunlight exposure duration as predictors and rice production as the target variable. The dataset was partitioned into training and testing subsets using an 80:20 ratio. Hyperparameter tuning was performed using k-fold cross-validation, and model performance was performed using Root Mean Squared Error (RMSE), Mean Absolute Error (MAE), Mean Absolute Percentage Error (MAPE), and the coefficient of determination (R²). The model attained an average RMSE of 93,046 tons (MAE ≈ 51,824 tons; MAPE ≈ 6.8% on the 2023 hold-out year). A key finding is that absolute RMSE is strongly scale-dependent. When evaluated in relative terms, the highest-producing Java provinces were among the most accurately predicted (relative RMSE ≈ 2.3–2.5%), whereas several small or structurally volatile provinces showed relative errors above 40%. The study contributes to the literature by providing (i) the explicit integration of sunlight exposure into Indonesian rice yield modeling, (ii) a province-disaggregated error analysis that reframes accuracy in scale-independent terms, and (iii) an interpretable decision-support tool for food-policy stakeholders such as Bulog and the Ministry of Agriculture.